Low dropout regulator with temperature coefficient curvature correction topology - Nardi, Utomo (2021)
The LDO Voltage Regulator circuit with temperature coefficient curvature correction topology is proposed in this paper. The LDO consists of a start-up circuit, a bias generator, a three-stage error amplifier, a power MOSFET, and a temperature coefficient curvature correction circuit. The circuit is simulated with 0.18μm CMOS Technology. The supply voltage can be as low as 800mV with the output voltage of 664mV. The proposed circuit obtains the temperature coefficient as low as 23.7ppm/°C for supply voltage ranging from 800mV until 1.5V. The lowest temperature coefficient of 6.1ppm/°C is obtained at 1.1V supply voltage. The temperature coefficient is measured for a wide range of temperature ranging from -50°C to 130°C. The stability is ensured from the simulation with high low-frequency open loop gain of above 105dB and high phase margin of above 100°.